Middle section of the Saptashakha of the Garbhagriha - Temples of India Project Team (Jio Institute, 2024)
The middle section of the saptashakha (seven vertical bands or architraves) of the garbhagriha (sanctum sanctorum) has five different patterns. The first, third, and fifth branches are decorated with floral designs. The second branch features carvings of nagas (serpents) arranged vertically, while the fourth branch, known as the stambha shakha, is a hexagonal pillar that transitions into a faceted shape before becoming circular. The sixth branch is adorned with sinuous floral patterns, while the final branch is also carved with a floral band.